Ultrasonographic and macroscopic comparison of the thickness of the capsule, corium, and soft tissues in bovine claws: anin vitrostudy - Cecen, Goksen; Salci, Hakan; Intas, Deniz Seyrek; Celimli, Nureddin; Caliskan, Gulsum Ulke (The Korean Society of Veterinary Science, 2015)
This study aimed to compare thickness of the capsule, corium, and soft tissues measured ultrasonographically and macroscopically in selected regions of bovine claws. A hundred and twenty claws (n = 120) of 15 healthy Holstein bovines were obtained. After cleaning the claws, ultrasonographic measurement of the capsule, corium, and soft tissues was performed while submerging the claws in a water bath. Macroscopic measurements were taken after cutting of the claws axially. These values were compared statistically. According to the macroscopic measurements, the mean thickness ± standard deviation (SD) of the capsule for dorsal wall and sole was 6.2 ± 0.1 and 9.5 ± 0.4 mm, respectively. The thickness of the corium and soft tissues for dorsal wall and sole was 4.5 ± 0.1 and 5.3 ± 0.1 mm, respectively. Ultrasonographically, the mean thickness ± SD of the capsule for dorsal wall and sole was 4.7 ± 0.1 and 7.8 ± 0.3 mm, respectively. The thickness of the corium and soft tissues for dorsal wall and sole was 4.3 ± 0.1 and 5.9 ± 0.2 mm, respectively. Findings demonstrated that ultrasonography can be reliably to measure of the thickness of the hoof capsule, corium, and soft tissue in bovine claw.
Keywords: Hoof and Claw; Cadaver; Animals; Original Article; Cattle; Ultrasonography